Dialetical Discourse on Development and Poverty: It’s Implication in Nigeria - Oduwole, Tajudeen Adebowale (Advances in Social Sciences Research Journal, 2016)
This paper crystally to a certain extent discusses the interrelationship between Development and Poverty as a social discourse. Principally, the paper x-rays the discourses, citing opinions of scholarly works from available academic literatures with a view of bringing to bear knowledge enhancement and contributing to the epistemology of academic exercise. Fundamentally the thrust of this paper is that “Development” is disentanglement or disengagement from poverty, while poverty is estrangement, an entanglement from development. Above all, its implication in Nigeria context, the paper posit holistically that before development (any meaningful ways of life) can take place, Nigeria people must count economically, politically, socially and nip in the bud poverty in all its ramifications.